A Pioneering Experiment Combining Single-antenna and Aperture-synthesis Data to Measure Faraday Rotation with GMIMS and the CGPS - Anna Ordog; Jo-Anne C. Brown; T. L. Landecker; Alex S. Hill; Roland Kothes; Jennifer L. West; John M. Dickey; Marijke Haverkorn; Ettore Carretti; Alec J. M. Thomson; Andrea Bracco; D. A. Del Rizzo; et al. (The Astronomical Journal)
Structures in the magnetoionic medium exist across a wide range of angular sizes owing to large-scale magnetic fields coherent over the Galactic spiral arms combined with small-scale fluctuations in the magnetic field and electron density resulting from energy injection processes such as supernovae. For the first time, we produce diffuse Galactic synchrotron emission Faraday rotation maps covering all spatial scales down to ${3}^{{′} }$ resolution for magnetic field studies. These maps complement total and polarized intensity maps combining single-antenna and interferometric data that have been produced, such as the Canadian Galactic Plane Survey (CGPS). Combined maps have sensitivity to large scales from the single-antenna component and angular resolution from the interferometric component. We combine Global Magneto-Ionic Medium Survey High-Band North single-antenna and CGPS aperture-synthesis polarization data after spatial filtering, producing Stokes Q and U maps for the four CGPS frequency channels. We calculate rotation measures (RMs) for all pixels using a linear fit to polarization angle versus wavelength squared. Smooth polarized emission regions require the large-scale sensitivity of the single antenna to illuminate the Faraday rotation, while aperture synthesis reveals small-scale RM variability. While these maps show magnetic field structures on the full range of spatial scales they probe, the RM values should be interpreted with caution, as the narrow λ ^2 coverage limits sensitivity to Faraday complexity. Despite this limitation of the CGPS 35 MHz bandwidth, we demonstrate that useful Faraday rotation information can be obtained from the combined data set, highlighting the important synergy between future broadband interferometric and single-antenna polarization surveys.